Studi Kelayakan Bisnis Pada PT. Bank Panin Dubai Syariah - Kamalia, Isna (Maliki Interdisciplinary Journal, 2025)
The company previously known as PT Bank Panin Syariah Tbk has officially changed its name to PT Bank Panin Dubai Syariah Tbk. This name change was carried out after a change in share ownership, where Dubai Islamic Bank became the new controlling shareholder. This name change has been stated in a notarial deed and has been approved by the Ministry of Law and Human Rights. Apart from that, the Financial Services Authority (OJK) has also given official permission for the use of this new name.